2008
DOI: 10.1007/s00432-008-0485-0
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics of participation in the opportunistic German cervical cancer screening programme: results from the EPIC-Heidelberg cohort

Abstract: Knowledge on the characteristics of women with a lower attendance to cervical cancer screening could be used to improve the effectiveness of the current (opportunistic) programme by dedicated health promotion programmes. However, an organized screening programme with written invitation of all eligible women would be the preferred option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 16 publications
4
20
2
4
Order By: Relevance
“…In the present study, the women who lived with their spouses were more likely to participate in cervical cancer screening. Similarly, married and cohabiting German and Norwegian women are more likely to get Pap tests than are those who are being single or living alone [24,25]. The results of this study were similar to another study of Latina women that found that those who had children were more likely to be maintainers [26].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the women who lived with their spouses were more likely to participate in cervical cancer screening. Similarly, married and cohabiting German and Norwegian women are more likely to get Pap tests than are those who are being single or living alone [24,25]. The results of this study were similar to another study of Latina women that found that those who had children were more likely to be maintainers [26].…”
Section: Discussionsupporting
confidence: 90%
“…Lower education or income and being unmarried or widowed have been related to lower screening participation in other studies (28)(29)(30); however, much of the difference in stage by educational level was not attributable to time since last smear in this study. Likewise, a study in New Zealand found that only a small proportion of the elevated risk for advanced cervical cancer of Maoris and of women in deprived areas (nonsignificant) was attributable to lack of screening participation (31).…”
Section: Discussioncontrasting
confidence: 70%
“…We found that the level of education was associated with the use of private PHEs but not with that of public PHEs, which contrasts with previous studies (Farrell and Fuchs 1982;Kenkel 2000). The level of education is thought to be an indicator of individuals' socioeconomic status (Seidel et al 2008). Indeed, inequalities in income and health status according to education level are larger in Korea than in developed countries (Khang et al 2004;Son 2004;Lee and Jeon 2005).…”
Section: Discussionmentioning
confidence: 99%